2000
DOI: 10.1180/002646100549878
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in perovskites near the tricritical point: an experimental study of KMn1–xCaxF3 and SrTiO3

Abstract: We present experimental data for the Pm3m I4/mcm phase transitions in the perovskite crystals KMn 1 x Ca x F 3 and SrTiO 3 . Comparison of calorimetric data (latent heat and specific heat) with order parameter data (measured with X-ray rocking methods) indicates that these transitions follow meanfield behaviour, and may be described using Landau potentials where the free energy expansion includes terms up to Q 6 . This potential is characteristic of transitions close to the tricritical point. Comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The doped samples had Ca concentrations of 0.3 mol % and 1.7 mol %. The samples are identical with those used previously by Gibaud et al, 18 Romero et al, 23 Gallardo et al, 22 and Salje et al 3 so that a direct comparison with their results is possible.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The doped samples had Ca concentrations of 0.3 mol % and 1.7 mol %. The samples are identical with those used previously by Gibaud et al, 18 Romero et al, 23 Gallardo et al, 22 and Salje et al 3 so that a direct comparison with their results is possible.…”
Section: Methodsmentioning
confidence: 86%
“…However, the temperatures of all phase transitions are enhanced by the substitution of Ca 2+ for the Mn 2+ ions. 22,23 It was argued 24,25 that the increase in T c with Ca content is the consequence of the larger ionic radius of the Ca 2+ ions ͓R͑Ca 2+ ͒ = 1.0 Å and R͑Mn 2+ ͒ = 0.83 Å since it is in high spin state 26 ͔ which forces a displacement of the fluorines off their symmetry positions and stabilizes the lower symmetry phase. We will show below that this mechanism also seems to create ͑100͒ dumbbell fluorine interstitials which could serve as pinning centers for the ferroelastic domain walls.…”
Section: Phase Transitions In Kmn 1−x Ca X Fmentioning
confidence: 97%
“…Furthermore, the effect of the substitution of Ca by Mn was also successfully investigated measuring the latent heat [12,14,15], which showed that the doping makes the transition shifts to second order.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-capacity measurements have been successfully used in the study of systems exhibiting doping-driven first-tosecond order change of the transition. [17][18][19] In these cases, highresolution heat-capacity measurements, for instance, through a precise accounting of the latent heat, 20 can determine the order of the transition extremely close to a tricritical point. 21,22 However, these kinds of high-resolution heat capacity measurements require a special setup and are very difficult to perform.…”
mentioning
confidence: 99%